Trauma promotes heparan sulfate modifications and cleavage that disrupt homeostatic gene expression in microvascular endothelial cells - Richter, Robert P.; Odum, James D.; Margaroli, Camilla; Cardenas, Jessica C.; Zheng, Lei; Tripathi, Kaushlendra; Wang, Zhangjie; Arnold, Katelyn; Sanderson, Ralph D.; Liu, Jian; Richter, Jillian R. (Frontiers in Cell and Developmental Biology, 2024)
Heparan sulfate (HS) in the vascular endothelial glycocalyx (eGC) is a critical regulator of blood vessel homeostasis. Trauma results in HS shedding from the eGC, but the impact of trauma on HS structural modifications that could influence mechanisms of vascular injury and repair has not been evaluated.Moreover, the effect of eGC HS shedding on endothelial cell (EC) homeostasis has not been fully elucidated. The objectives of this work were to characterize the impact of trauma on HS sulfation and determine the effect of eGC HS shedding on the transcriptional landscape of vascular ECs. Plasma was collected from 25 controls and 49 adults admitted to a level 1 trauma center at arrival and 24 hours after hospitalization. Total levels of HS and angiopoietin-2, a marker of pathologic EC activation, were measured at each time point. Enzymatic activity of heparanase, the enzyme responsible for HS shedding, was determined in plasma from hospital arrival. Liquid chromatography-tandem mass spectrometry was used to characterize HS di-/tetrasaccharides in plasma. In vitro work was performed using flow conditioned primary human lung microvascular ECs treated with vehicle or heparinase III to simulate human heparanase activity. Bulk RNA sequencing was performed to determine differentially expressed gene-enriched pathways following heparinase III treatment. We found that heparanase activity was increased in trauma plasma relative to controls, and HS levels at arrival were elevated in a manner proportional to injury severity. Di-/tetrasaccharide analysis revealed lower levels of 3-O-sulfated tetramers with a concomitant increase in ΔIIIS and ΔIIS disaccharides following trauma. Admission levels of total HS and specific HS sulfation motifs correlated with 24-hour angiopoietin-2 levels, suggesting an association between HS shedding and persistent, pathological EC activation. In vitro pathway analysis demonstrated downregulation of genes that support cell junction integrity, EC polarity, and EC senescence while upregulating genes that promote cell differentiation and proliferation following HS shedding. Taken together, our findings suggest that HS cleavage associated with eGC injury may disrupt homeostatic EC signaling and influence biosynthetic mechanisms governing eGC repair. These results require validation in larger, multicenter trauma populations coupled with in vivo EC-targeted transcriptomic and proteomic analyses.